2017
DOI: 10.5194/acp-17-9067-2017
|View full text |Cite
|
Sign up to set email alerts
|

A wedge strategy for mitigation of urban warming in future climate scenarios

Abstract: Abstract. Heat stress is one of the most severe climate threats to human society in a future warmer world. The situation is further exacerbated in urban areas by urban heat islands (UHIs). Because the majority of world's population is projected to live in cities, there is a pressing need to find effective solutions for the heat stress problem. We use a climate model to investigate the effectiveness of various urban heat mitigation strategies: cool roofs, street vegetation, green roofs, and reflective pavement.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
(100 reference statements)
0
33
2
Order By: Relevance
“…This indicates negative feedbacks between UHI 2m and HWs in a future warmer world. Although our analysis and previous studies ( Oleson 2012, Zhao et al 2017 have shown that different RCP scenarios have different impacts on the UHI, we find only slight difference in UHI 2m -HW interactions between the two climate scenarios (figure 3(a)). The reason might lie in the calculation of the synergistic effects of HW and UHI.…”
Section: Interactions Between Uhi 2m and Hwscontrasting
confidence: 90%
See 1 more Smart Citation
“…This indicates negative feedbacks between UHI 2m and HWs in a future warmer world. Although our analysis and previous studies ( Oleson 2012, Zhao et al 2017 have shown that different RCP scenarios have different impacts on the UHI, we find only slight difference in UHI 2m -HW interactions between the two climate scenarios (figure 3(a)). The reason might lie in the calculation of the synergistic effects of HW and UHI.…”
Section: Interactions Between Uhi 2m and Hwscontrasting
confidence: 90%
“…We computed UHI 2m (ΔT 2m ) and UHI s (ΔT s ) from the variables generated by the urban and rural sub-grids in the grid cells where our selected cities are located (please see the supplementary information for more details). Although the UHI 2m and UHI s differ in various aspects and their magnitudes are not directly comparable (Arnfield 2003), the two UHIs show consistency in terms of the linear supposition property of their biophysical contributions (Zhao et al 2017). One merit of UHI s compared to UHI 2m is that the former has a firm and yet simple theoretical basis derived from the surface energy balance principle that underpins the biophysical factorization (described in the next section).…”
Section: Uhi Analysismentioning
confidence: 99%
“…UHI mitigation strategies may need to be targeted at populations that have the greatest need due to their disproportionate exposure or low capacity to cope with the associated health effects. There is evidence that combining multiple UHI mitigation strategies can effectively negate the localized warming due to both UHI and climate change (Zhao et al 2017). In an increasingly urbanized future, intertwining different UHI mitigation strategies can potentially transform cities into havens of climate adaptation, since city-level policy making can bypass constraints often present at other government levels (Hoffmann 2011, Hsu et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…While many others factors, like anthropogenic heat flux, longwave trapping by urban canyons, aerosols, etc can modulate the UHI (Taha 1997, Zhao et al 2014, Li et al 2018, two of the factors considered in this study account for the vast majority of UHI mitigation measures; green roofs and green spaces modulate NDVI, while white roofs and reflective pavements alter α (Rizwan et al 2008, Zhao et al 2017. The third factor, NDBI, is the UHI's most direct cause since it is a proxy for the degree of urbanization.…”
Section: Data Processingmentioning
confidence: 92%
“…Such measurements may be especially useful in situations where monitoring with conventional radiometers is not feasible. For example, white roofs are proposed as a strategy to mitigate the urban heat island in the city landscape [41]. However, white paint on building roofs can suffer from erosion and dust deposition, and thus, its albedo can quickly decrease, from the original high values of 0.7 to 0.8 to values of 0.2 to 0.3 after a few years [42].…”
Section: Potential Applicationsmentioning
confidence: 99%